Language and Socio-Emotional Development of Children with Speech Delays: Analysis of Gadget Use - Fitriyani Fitriyani; Awalina Barokah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
It is crucial to describe language development and socio-emotional behavior in children with speech delays. Many cases of speech delays in children are caused by the use of gadgets. Early detection of language and speech development problems, intervention programs carried out, and academic and socio-emotional development of children with speech and language disorders will greatly help overcome these problems. This study was conducted to describe language development and socio-emotional behavior in children with speech delays caused by the use of gadgets, early detection of language and speech development problems, intervention programs carried out, and academic and social-emotional development of children with speech and language disorders. The research was based on observations of a 9-year-old child, conducted from September 2018 to January 2019, with data collection since 2012 when language and speech disorders were early detected. The research applied a qualitative approach, with a case study method, while the data collection was through observation, interviews, and documentary studies. This study’s findings showed that the socio-emotional behavior caused by the influence of the gadget use had a major effect on children's development with speech delay problems; thus, an appropriate intervention program is needed for the family and environment. These results have implications for helping children with language and speech problems, not only being strictly allowed to use gadgets but also directed to obtain stimuli to reduce excessive socio-emotional levels in these children.